High expression of CD38 and MHC class II on CD8+ T cells during severe influenza disease reflects bystander activation and trogocytosis. Issue 9 (8th September 2021) - Jia, Xiaoxiao; Chua, Brendon Y; Loh, Liyen; Koutsakos, Marios; Kedzierski, Lukasz; Olshansky, Moshe; Heath, William R; Chang, So Young; Xu, Jianqing; Wang, Zhongfang; Kedzierska, Katherine
Abstract: Objectives: Although co‐expression of CD38 and HLA‐DR reflects T‐cell activation during viral infections, high and prolonged CD38 + HLA‐DR + expression is associated with severe disease. To date, the mechanism underpinning expression of CD38 + HLA‐DR + is poorly understood. Methods: We used mouse models of influenza A/H9N2, A/H7N9 and A/H3N2 infection to investigate mechanisms underpinning CD38 + MHC‐II + phenotype on CD8 + T cells. To further understand MHC‐II trogocytosis on murine CD8 + T cells as well as the significance behind the scenario, we used adoptively transferred transgenic OT‐I CD8 + T cells and A/H3N2‐SIINKEKL infection. Results: Analysis of influenza‐specific immunodominant D b NP366 + CD8 + T‐cell responses showed that CD38 + MHC‐II + co‐expression was detected on both virus‐specific and bystander CD8 + T cells, with increased numbers of both CD38 + MHC‐II + CD8 + T‐cell populations observed in immune organs including the site of infection during severe viral challenge. OT‐I cells adoptively transferred into MHC‐II −/− mice had no MHC‐II after infection, suggesting that MHC‐II was acquired via trogocytosis. The detection of CD19 on CD38 + MHC‐II + OT‐I cells supports the proposition that MHC‐II was acquired by trogocytosis sourced from B cells. Co‐expression of CD38 + MHC‐II + on CD8 + T cells was needed for optimal recall following secondary infection. Conclusions: Overall, our study demonstrates that both virus‐specific and bystander CD38 + MHC‐II + CD8 + T cells are recruited to the site of infection during severe disease, and that MHC‐II presence occurs via trogocytosis from antigen‐presenting cells. Our findings highlight the importance of the CD38 + MHC‐II + phenotype for CD8 + T‐cell recall. Abstract : Severe H7N9 infection in mice induces CD38 + MHC‐II + PD‐1 + activation profiles. These data reflect findings from H7N9‐hospitalised patients with severe and fatal disease outcomes.